The Role of Constitutional Judiciary in Protecting the Right to Sustainable Development in Iraq - Zeki Noori Ayash , Assist. Prof. Suha (Basra studies journal, 2023)
The topic of sustainable development has garnered significant attention in the past two decades, given the newly emerging financial and social problems and crises globally, affecting countries, including Iraq, to varying degrees. This prompted the world to adopt theories, mechanisms, and guarantees aimed at achieving social justice, environmental protection, and sustainable growth that preserves the rights of future generations. One of the significant challenges highlighted in this study is the absence of constitutional and legal regulations governing the right to sustainable development in Iraq. The constitutional judiciary in Iraq plays a fundamental and effective role in protecting the right to sustainable development through crucial elements such as the independence, integrity, and neutrality of the judiciary, ensuring justice, safeguarding rights and freedoms, and implementing the principle of legitimacy. This, in turn, contributes to achieving sustainable development. Additionally, its role in overseeing the constitutionality of laws serves as a regulator for societal progress in various fields. Respecting human rights, including the right to sustainable development, is an essential element in building civil and democratic societies.